Assessment of Incidence of Allergic Rhinitis in Chronic Rhinosinusitis Patients: A Prospective Analysis - Mumtaz Ahmad Umar; Ayesha Jawad; Mirza Nasheed Baig; Nighat Arif; Saira Iftikhar; Mohibullah Mushwani (Journal of Aziz Fatimah Medical and Dental College)
Objective: The study aims to assess the incidence of allergic rhinitis and prevalent allergens among individuals with chronic rhinosinusitis.